Strategi Dinas Perhubungan Menerapkan Regulasi Angkutan Online Dalam Menambah Pendapatan Asli Daerah (PAD) Di Kota Palangka Raya: The Strategy Of The Transportation Service To Apply Online Transport Regulation In Adding Indigenous Revenue (PAD) In The City Palangka Raya - Hidayat, Rahmat; Diani, Diani (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2019)
Public transport is transport from one place to another within the general region by using public bus cars and public passenger cars that are bound to the route remains organized. While online transport is one of the traffic and road transport events that rely on and utilize the development of science and technology. A transport device that uses a private vehicle associated with an application. The objectives of this research for the Transportation Service strategy apply the regulation of online transport in increasing the regional original income in the city of Palangkaraya. And to find out what are the positive and negative impacts of the Transportation Service strategy to apply the regulation of online transport in increasing the regional original revenue in the city of Palangkaraya. During this time the online transport has no permission (illegal) to operate which is one aspect that raises the prolonged conflict between online and public transport. Because of the impact on regional indigenous revenue since many entrepreneurs-public transport entrepreneurs may have moved to online transport. PM No. 118 the year 2018 about special rental transport is the current regulation. The research uses qualitative methods that generate descriptive data on spoken and written words. And the results of the authors of research found that the Department of Transportation has not implemented new online transport regulations because it does not have the operation license of municipal government Palangka Raya does not get retribution of the online transport with There is no additional regional income in the city of Palangka Raya.